Fluorescence Differentiation of ATP-related Multiple Enzymatic Activities in Synovial Fluid as a Marker of Calcium Pyrophosphate Deposition Disease using Kyoto Green - Nattha Yongwattana (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/). Calcium pyrophosphate deposition disease (CPPD) is a crystal induced inflammation in joints, and causes severe pain in elderly people. The accumulation of pyrophosphate (PPi) in synovial fluid (SF) results from several enzymatic reactions, especially the highly activated e-NPPs, which catalyze the conversion of ATP to PPi. This study demonstrates the detection of relative catalytic activity of 3 enzymes—ecto-nucleotide pyrophosphatase/phosphodiesterases (e-NPPs), tissue nonspecific alkaline phosphatase (TNAP), and ecto-nucleoside triphosphate diphosphohydrolases (e-NTPDases)—using a single molecular sensor called Kyoto Green. Kyoto Green exhibits excellent performance in sensing the catalytic activity of the commercial representatives of the e-NPPs, TNAP, and e-NTPDases, which are ENPP1, PPase, and apyrase, respectively, in both single-enzyme and multi-enzyme assays. Analysis of SF enzymes in 19 SF samples from human and swine revealed moderate activity of e-NPPs, high activity of e-NTPDases, and low activity of TNAP. Our newly developed method for analysis of multiple enzymatic activities using Kyoto Green in biological SF will assist improvement in accuracy of the CPPD prognosis/diagnosis, which will minimize unnecessary medical procedures.